2021
DOI: 10.25299/sportarea.2021.vol6(3).6569
|View full text |Cite
|
Sign up to set email alerts
|

The differences in Papuan elite athletes in the anxiety perspective

Abstract: Anxiety is believed to be an important psychological dimension in determining the outcome of sport matches. However, studies examining this aspect of Papuan elite athletes have never been conducted. Therefor, this study aims to reveal the differences in the anxiety amidst the Papuan elite athletes in terms of sport and gender. Furthermore, the comparative research method used involves six sports with different characteristics, namely game, martial arts, and accuracy. Subsequently, a total of 100 athletes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…The tenth was on managing anxiety and this section also had appropriate had excellent score from all experts. Anxiety is a normal condition for humans 30 and this often appears in the context of sports 88,89 so that the athletes' anxiety dimension is often studied by associating it to other aspects. 90 In general, the factors that cause anxiety for athletes can be grouped into two aspects, namely internal and external factors.…”
Section: Discussionmentioning
confidence: 99%
“…The tenth was on managing anxiety and this section also had appropriate had excellent score from all experts. Anxiety is a normal condition for humans 30 and this often appears in the context of sports 88,89 so that the athletes' anxiety dimension is often studied by associating it to other aspects. 90 In general, the factors that cause anxiety for athletes can be grouped into two aspects, namely internal and external factors.…”
Section: Discussionmentioning
confidence: 99%
“…This study found no difference in the psychological abilities of athletes because Indonesian National Sports Committee made a policy or program called "Character Building and Achievement Motivation Training" (CB-AMT) by involving experts in the field of sports psychology. Furthermore, the program's main objective was to form a winning mentality for Papuan athletes [54]. All those undergoing training were required to participate in the CB-AMT.…”
Section: Discussionmentioning
confidence: 99%
“…Meskipun berlabel sebagai event terbesar olahraga nasional, kajian terkait PON belum banyak dilakukan. Bagi sebagian kalangan peneliti, dimensi yang bertalian dengan aspek prestasi, psikologi, dan fisik menjadi dimensi yang kerap dikaji (lihat misalnya: Mangolo et al, 2021;Putra & Ita, 2019;Maulana & Khairani, 2017;Ikhsan et al, 2016;Purba, 2016). Hal ini terjadi karena dimensi tersebut dipandang akan memberikan dampak langsung pada atlet dan prestasi (Thomson et al, 2019).…”
Section: Pendahuluanunclassified